2017
DOI: 10.1002/jcb.25910
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC2 Interacts With miR‐181a to Modulate Glioma Growth and Resistance to TMZ Through PTEN Pathway

Abstract: Temozolomide (TMZ)-based chemotherapy is a standard strategy for glioma, while chemoresistance remains a major therapeutic challenge. Recent evidence highlights the crucial regulatory roles of long non-coding RNAs (lncRNA) in tumor biology. However, the roles and regulatory mechanisms of lncRNA cancer susceptibility candidate 2 (CASC2), in glioma tumorigenesis and chemoresistance are poorly understood. In this study, CASC2 expression was down-regulated in glioma tissues and cell lines, and was related to a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(128 citation statements)
references
References 34 publications
5
123
0
Order By: Relevance
“…For example, lncRNA MALAT1 was reported to directly bind to miR-204 and upregulated its target gene CXCR4 in hilar cholangiocarcinoma. 21 In this study, our data indicated that DQ786243 promoted ovarian cancer-cell growth through miR-506dependent CREB1 regulation. 20 Moreover, lncRNA CASC2 could interact with miR-181a to modulate glioma growth through PTEN pathway.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…For example, lncRNA MALAT1 was reported to directly bind to miR-204 and upregulated its target gene CXCR4 in hilar cholangiocarcinoma. 21 In this study, our data indicated that DQ786243 promoted ovarian cancer-cell growth through miR-506dependent CREB1 regulation. 20 Moreover, lncRNA CASC2 could interact with miR-181a to modulate glioma growth through PTEN pathway.…”
Section: Introductionmentioning
confidence: 51%
“…20,21,27,28 Therefore, we further investigated whether miR-506 could directly regulate CREB1 in ovarian cancer. 20,21,27,28 Therefore, we further investigated whether miR-506 could directly regulate CREB1 in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CASC2 was reported to be involved in some classical signaling pathways to function as a tumor suppressor 11,19. Wnt/β-catenin signaling pathway is a highly conserved molecular mechanism which was reported to play a crucial role in a variety of human malignancies, including ovarian cancer, hepatocellular carcinoma, breast cancer, and colorectal cancer, by activating its downstream targets including Cyclin D1, c-Myc, GSK-3, and so on 20–23.…”
Section: Discussionmentioning
confidence: 99%
“…These cancers ranged from an early stage to advanced clinical stages (I, II, III, and IV). Of the 8 studies, 3 included a follow-up of greater than or equal to 60 months [23, 27, 28]; the remaining 5 studies covered less than 5 years [21, 22, 24-26]. The expression of lncRNA CASC2 in all eligible studies was measured by quantitative real-time polymerase chain reaction (qRT-PCR) and normalized relative to GAPDH or RNU6B using the 2 –ΔΔCt method.…”
Section: Resultsmentioning
confidence: 99%